Applications of digital PCR in precision medicine. Issue 3 (4th May 2017) - Wong, Y. K.; Tsang, H. F.; Xue, V. W.; Chan, C. M.; Au, T. C.; Cho, W. C.; Chan, L. W.; Wong, S. C.
ABSTRACT: Introduction : Polymerase chain reaction (PCR) has been a reliable molecular technology in both research and clinical fields for decades. It amplifies a minute amount of DNA or RNA sample into large quantity for target detection. Recently, a more advanced molecular manifestation, digital PCR (dPCR), has become popular in molecular diagnostics as it has potential advantages against quantitative PCR (qPCR) and this technology will become a mainstream diagnostic platform in future. Areas covered : This review describes the principle and types of dPCR, and its potential applications on different aspects and fields. Expert commentary : Digital PCR is an advanced molecular testing technology that has massive potential. Its improved accuracy and precision help diagnosing various diseases at an earlier stage, monitoring treatment in higher resolution and hence raising the recovery rate and survival rate of patients. However, to put dPCR into routine clinical application, it is very important to ensure that dPCR is robust and cost-effective so as to build up confidence and interest in the molecular diagnostic field. When dPCR can increase its throughput with excellent accuracy, sensitivity, robustness and reproducibility, it will eventually take on a major role in the diagnosis, prognosis and therapeutics in the precision medicine era.